The Effect of Transformational Leadership Behavior on Organizational Culture: An Application in Pharmaceutical Industry - Sinem Aydogdu; Baris Asikgil (International Review of Management and Marketing, 2011)
In this study, conducted on 96 employees from production sector in a pharmaceutical company, the effect of transformational leadership behavior on organizational culture is investigated to determine statistically significant relations. The results of the study support the hypotheses. Transformational leadership behavior has a positive and significant correlation between the components of organizational culture such as long / short term orientation, masculinity / feminity, power distance, individualism / collectivisim and uncertainity avoidance.